Answer:
88.98 %.
Explanation:
- From the balanced equation:
<em>2HCl + Pb(NO₃)₂ → 2HNO₃ + PbCl₂</em>
- It is clear that 1.0 mole of Pb(NO₃)₂ reacts with 2.0 moles of HCl to produce 1.0 mole of PbCl₂ and 2.0 moles of HNO₃.
- <em>The percent yield % of lead(II) chloride (PbCl₂) = [(actual yield) / (calculated yield)] x 100.</em>
- The actual yield of lead(II) chloride (PbCl₂) = 650 g.
- Now, we need to calculate the calculated yield of lead(II) chloride (PbCl₂).
- We need to calculate the no. of moles (n) of lead(II) nitrate (Pb(NO₃)₂) (870 grams) using the relation: <em>n = mass / molar mass.</em>
- n of lead(II) nitrate (Pb(NO₃)₂) = mass / molar mass = (870 g) / (331.2 g/mol) = 2.63 mol.
- Since HCl is in excess, the limiting reactant is lead(II) nitrate (Pb(NO₃)₂).
<u><em>Using cross multiplication:</em></u>
1.0 mole of Pb(NO₃)₂ produces → 1.0 mole of PbCl₂, from the stichiometry.
∴ 2.63 mole of Pb(NO₃)₂ produces → 2.63 mole of PbCl₂.
- The mass of PbCl₂ produced (the calculated yield) = n x molar mass = (2.63 mol) (278.1 g/mol) = 730.52 g.
∴ The percent yield % of lead(II) chloride (PbCl₂) = [(actual yield) / (calculated yield)] x 100 = [(650 g) / (730.52)] x 100 = 88.98 %.
Answer:
The answer to your question is below
Explanation:
Data
pOH = 5.9
a) [OH⁻] = ?
pOH measures the [OH⁻]
Formula
pOH = -log[OH⁻]
-Substitution
5.9 = -log[OH⁻]
[OH⁻] = antilog (-5.9)
-Result
[OH⁻] = 1.26 x 10⁻⁶ M
b) [H₃O⁺]
pH + pOH = 14
-Solve for pH
pH = 14 - pOH
-Substitution
pH = 14 - 5.9
-Result
pH = 8.1
-Calculate [H₃O⁺]
pH = -log[H₃O⁺]
-Substitution
8.1 = -log[H₃O⁺]
[H₃O⁺] = antilog(-8.1)
-Result
[H₃O⁺] = 7.9 x 10⁻⁹ M
c) This solution is alkaline because the pH is higher than 7.
I think the correct answer is D
The picture is not loading as it requires a sign in.
However, I can tell you how to solve this.
Answer:
<span>As the wavelength gets shorter (closer together), the frequency of the wave increases.
Explanation:
The relation between frequency and wavelength can be described by the help of velocity as follows:
velocity = frequency * wavelength
This means that:
frequency = velocity / wavelength
Noting this equation, we will find that:
The frequency and the wavelength are inversely proportional to each other. This means that as the frequency increases, the wavelength decreases and vice versa.
Now, examining the choices given, we can find that the only statement showing the inverse relation between frequency and wavelength is:
</span><span>As the wavelength gets shorter (closer together), the frequency of the wave increases.
Hope this helps :)
</span>